BUSINESS OPERATIONS MANAGEMENT OF “TEXNOMART - Ozodbekova Azizakhon Pulatjon qizi (Modern American Journals, 2025)
Today, people utilize a range of services to simplify their daily lives. Almost all major corporations offer their customers both online and offline services through their websites, applications, or in-person interactions with specialists who provide the necessary goods (Xu et al., 2014). Texnomart, a distributor of retail electronics, laptops, smartphones, appliances, and other products, is one of the leading companies offering both types of services in Uzbekistan.The company was established in 2008 to offer high-quality electronics at affordable and competitive prices to reach a wide customer base.